KARAKTERISITIK FISIKOKIMIA BIHUN BERAS SUBSTITUSI PARSIAL TEPUNG RUMPUT LAUT Eucheuma cottoni - Hardoko, Mr.; Chamidah, Anies; Panjaitan, Mikchaell A.P.; Haryady, Ain Nun Fakhur (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2021)
Noodle vermicelli is one of Indonesia's traditional noodle products made from rice flour and the vermicelli is characterized by breaking easily. This research aimed to make the vermicelli stronger and more fibrous by substituting E cottonii seaweed. The method used was an experimental method in the form of E cottonii substitution treatment of 25%, 30%, and 35% w / w. The results show that the substitution of E cottonii seaweed in the manufacture of vermicelli noodles can increase the power of vermicelli breaking, rehydration power, and the color of the vermicelli becomes red (oHue 42,35-44,53), but the brightness decreases. The most preferred substituted vermicelli is substituted with 25% E. cottonii with a preference level of 3.55 (likes) from a hedonic scale of 1-5. The substituted vermicelli noodles with E cottonii were selected to meet SNI 01-2975-2006, fracture strength 3.03N (increase by 11.4%), water absorption capacity 128.42% (increase 68.6%), and yield 54.80%, and contains 6.26% dietary fiber.